INTENSITAS NYERI DAN KECEMASAN PASIEN PASCA OPERASI - Ahmad Rosuli; Agnes Murindra Prasetyo; Rudiyanto Rudiyanto; Rani Diana Balqis (Jurnal Penelitian, 2022)
Introduction: The pain experienced by pascaoperative patients is subjective, where each patient has a different level of pain. The level of pain arises causing pascaoperative patients to feel increased anxiety. This study aims to analyze the relationship of pain intensity with anxiety in pascaoperative patients in the treatment room of AL HUDA Tile Hospital by 2021. Method: correlational with cross sectional approach. Accidental sampling technique consists of 66 pascaoperative patient respondents. Rank Spearman's statistical test. The data collection used questionnaires on NRS to measure pain intensity and HARS questionnaires to measure anxiety levels in pascaoperative patients. Results: of statistical test calculation Rank Spearman SPSS version 16 obtained correlation Coefficient 0.640 and sig (2 tailed) = 0.000 0.05 level (2-tailed) there is a relationship of pain intensity with anxiety in pascaoperative patients in the treatment room al HUDA Tile Hospital in 2021, resulting in a correlation coefficient of 0.640 strong objection level between pain intensity and anxiety levels in patients pasca surgery. Analysis: Results from the intensity of pascaoperative patient pain most pascaoperative patients experienced severe pain, which was 38 respondents (57.6%). While in the results of anxiety in pascaoperative patients almost as close as pascaoperative patients experience severe anxiety, which is a number of 32 respondents (48.5%). Conclusion: Pascaoperative patients will feel pain from the effects of surgery performed so that it can cause anxiety effects, perform implementation to reduce pain and provide clear information related to actions taken against patients properly to reduce anxiety in pascaoperative patients.